Cocoa Seedling Cultivation (Theobroma Cacao) Using Bokashi Fertilizer Media as an Environmentally Friendly Solution - Huda, Miftahul; Afif, Mufti; Djayusman, Royyan Ramdhani; Rachmat, Arie (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This community service project, conducted in Bugel Hamlet, Karangrejo Village, focuses on improving cocoa farming through the use of bokashi fertilizer as an environmentally friendly alternative to chemical fertilizers. The project aims to enhance soil fertility and cocoa seedling growth while promoting sustainable agricultural practices. Using Participatory Action Research (PAR), local farmers were actively involved in the planning, implementation, and evaluation phases. The research methodology included observation, interviews, and field studies. Results showed that bokashi fertilizer significantly improved soil health, increased cocoa productivity, and fostered a better balance of soil microorganisms compared to chemical fertilizers. The project empowered local farmers by providing them with an eco-friendly solution for enhancing cocoa farming, with the potential to increase productivity, support local economic growth, and contribute to long-term environmental sustainability.